IRF och den svenska rymdforskningen : Transkript av ett vittnesseminarium på Institutet förrymdfysik i Kiruna den 16 november 2017 - Emanuel, Martin (KTH, Urbana och regionala studier, 2018)
The witness seminar “IRF och den svenska rymdforskning-en” (IRF and Swedish space research) was held at IRF (Insti-tutet för rymdfysik, The Swedish Institute of Space Physics) in Kiruna on November 16, 2017, and was led by Martin Emanuel and Johan Kärnfelt. The seminar covered three themes: key events in the history of the institute; the funding structures of Swedish space-related research; and issues con-cerning instrumentation of space physics experiments. Vari-ous key events were proposed, ranging from contingencies in the establishment of the institute in 1957 to the institute’s en-gagement in ESRO’s very first scientific satellites, the Swe-dish-Soviet research collaborations initiated in the 1970s, and the Swedish scientific satellite Viking launched in 1986. The 1960s was a difficult decade for Swedish space-related re-search, with most national funding channelled through the European Space Research Organisation (ESRO). Since ESRO prioritized satellite programmes, the institute—as the only Swedish group with experience of satellites—fared well compared to other research groups. The institute came to dominate Swedish space physics. In the period 1970–1994, the first director of the institute also chaired the scientific committee of the Swedish research councils (Forskningsrådens rymdnämnd) until 1972, and then of the Swedish National Space Board (Statens delegation för rymdverksamhet). The issue of potential bias and conflict of interest was discussed. Whereas some panellists stressed the fair, smooth and non-conflicting nature of the situation, others argued that certain groups felt discriminated. The participants often mentioned the im-portance of having in-house engineering skills at the institute: it was cheaper, made possible the long-term build-up of competence, and allowed for the immediate collaboration be-tween the scientists and the engineers in the design of exper-iments. In contrast, many other groups relied on the technical expertise of the Swedish Space Corporation (SSC; Rymdbo-laget). The ...